1998
DOI: 10.1074/jbc.273.20.12650
|View full text |Cite
|
Sign up to set email alerts
|

Stability Determinants Are Localized to the 3′-Untranslated Region and 3′-Coding Region of the Neurofilament Light Subunit mRNA Using a Tetracycline-inducible Promoter

Abstract: The tetracycline-responsive expression system of Bujard was used to compare rates of decay of wild-type and mutant neurofilament (NF) light subunit (NF-L) mRNAs. Optimal conditions for activation and inactivation of the target transgene were determined using a luciferase reporter gene. Analyses of mRNA stability were thereupon conducted on cells that were doubly transfected with transactivator and inducible target genes and derived from pooled clones of transfected cells. Rates of mRNA decay were compared upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 27 publications
(34 reference statements)
0
27
0
Order By: Relevance
“…Murine NFL mRNA cis-acting elements are present in the 3Ј-coding region (3Ј-CR) and 3Ј-UTR of the NFL mRNA (18,19). Deletion of the 3Ј-UTR or 527 nt of the 3Ј-CR increased the stability of murine NFL mRNA compared with the full-length transcript in cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Murine NFL mRNA cis-acting elements are present in the 3Ј-coding region (3Ј-CR) and 3Ј-UTR of the NFL mRNA (18,19). Deletion of the 3Ј-UTR or 527 nt of the 3Ј-CR increased the stability of murine NFL mRNA compared with the full-length transcript in cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Cloning and Expression of hNFL Genes-Because of the limitations in the length of an RNA probe for RNA-protein binding assays, the last 1000 nt of hNFL mRNA, including the 3Ј-untranslated region (hNFL-1000), which contains the putative major stability regulatory elements (18), was RT-PCR amplified from an ALS patient RNA sample and cloned into pcDNA3.1(ϩ) as the representative for the full-length hNFL (16). hNFL cDNA devoid of the 3Ј-untranslated region (hNFL-CDS) was also amplified and cloned.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that a 68 nucleotide (nt) segment of the NF-L mRNA was essential for NF-L mRNA stabilization in neuronal cells (Cañete-Soler et al, 1998a) (Fig. 1 A).…”
Section: Identification Of Neuronal Aldolases a And C As Neurofilamenmentioning
confidence: 99%
“…Messenger RNA is a key molecule in cell biology and the control of transcription plays a critical role in gene expression+ It is not, however, simply the rate of production but the rate of mRNA decay that controls gene expression within cells+ In most instances, mRNA stability and expression are effected by interplay of cisacting elements in the nucleic acid with RNA-binding proteins acting in trans+ Control of these RNA-protein interactions is not just fundamentally important to our understanding of cell biology, but is important in the pathogenesis of disease+ Changes in mRNA stability, for example, have been implicated in the etiology of several neurological disorders (Amara et al+, 1999;Canete-Soler et al+, 1999), rheumatoid arthritis (Jeddi et al+, 1994), and systemic scleroderma (Eckes et al+, 1996)+ Differences in stability can vary over several orders of magnitude, with half-lives ranging from several minutes for human lymphokine and cytokine mRNAs (Ross, 1995), to many hours for transcripts encoding members of the globin family (Weiss & Liebhaber, 1995) or respiratory chain components (ChrzanowskaLightowlers et al+, 1994)+ Stabilities of numerous mRNA species are known to be regulated in response to many forms of external stimuli, during development or at certain stages of the cell cycle+ In most instances, it is the 39 UTR that harbors the cis-acting sequences that are important in stability (Chkheidze et al+, 1999;Jacobs Anderson & Parker, 2000;Mitchell & Tollervey, 2000), although examples outside this region have been identified (Canete-Soler et al+, 1998)+ Since the observation that an AU-rich element introduced into the 39 UTR of transcripts could mediate selective mRNA degradation (Shaw & Kamen, 1986), research has focused on characterizing this element (Chen & Shyu, 1995;Rajagopalan & Malter, 1996;Di Noia et al+, 2000), the trans-acting proteins (SelaBrown et al+, 2000), and their importance in regulating mRNA decay+ Although the factors defining rapid degradation began to be identified a decade ago (Shaw & Kamen, 1986), less has been achieved in identifying determinants that increase transcript stability+ Polypyrimidine elements have been found in the 39 UTRs of several long-lived mRNA species (Czyzyk-Krzeska & Beresh, 1996)+ Additionally, a family of poly-C binding proteins with homology to the hnRNP K polypeptides were shown to bind to the 39 UTR stability element in b-globin mRNA (Chkheidze et al+, 1999)+ Originally found in erythroid cells, this family of poly-C bindin...…”
Section: Introductionmentioning
confidence: 99%